2015
DOI: 10.5120/21722-4873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variable Viscosity and Thermal Conductivity on MHD Flow of Micropolar Fluid in a Continuous Moving Flat Plate

Abstract: Effects of temperature dependent viscosity and thermal conductivity on magnetohydrodynamic flow and heat transfer over a continuous moving plate of a micropolar fluid have been studied. The fluid viscosity and thermal conductivity are assumed to be vary as inverse linear functions of temperature. Using similarity transformations the governing partial differential equations of motion are reduced to ordinary ones, which are solved numerically for prescribed boundary conditions using shooting method. Numerical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The tiny size nanoparticles are useful to carry the slip velocity within the partcles of conventional fluids [9]. Various researchers have shown that particle rotation is also vital for the enhancement of heat transfer coefficient [10][11][12][13]. Due to the slip velocity of nanoparticles with the base fluid molecules, there is a possibility of microrotation in addition to the translation.…”
Section: Introductionmentioning
confidence: 99%
“…The tiny size nanoparticles are useful to carry the slip velocity within the partcles of conventional fluids [9]. Various researchers have shown that particle rotation is also vital for the enhancement of heat transfer coefficient [10][11][12][13]. Due to the slip velocity of nanoparticles with the base fluid molecules, there is a possibility of microrotation in addition to the translation.…”
Section: Introductionmentioning
confidence: 99%
“…Nitt [12] derived the boundary layer theory which was important in the light of a number of technical processes. Oianrewaju [15], Hazarika and Phukan [10] and also many researchers studied the behaviour of micropolar fluids in steady state on different environments. Hayat [18], El Aziz [14],], Thakur et al [16 ] , Baruah and Hazarika [11] studied Micropolar fluids in the unsteady state.…”
Section: Introductionmentioning
confidence: 99%